Real wealth and experimental cooperation: experiments in the field lab. - Cardenas, Juan-Camilo (Journal of Development Economics, 2003)
This paper explores how wealth and inequality can affect self-governed solutions to commons dilemmas by constraining group cooperation. It reports a series of experiments in the field where subjects are actual commons users. Household data about the participants' context explain statistically the usually observed wide variation found within and across groups in similar experiments. Participants' wealth and inequality reduced cooperation when groups were allowed to have face-to-face communication between rounds. There are implications for a greater awareness of nonpayoff asymmetries affecting cooperation in heterogeneous groups, apart from heterogeneity in the payoffs structure of the game. Copyright (c) 2003 Elsevier Science B.V.